THU0625 Healthcare Professionals' Perspectives on The Design and Implementation of An Early Integrated Care Intervention for Musculoskeletal Pain in The Irish Healthcare Setting: A Qualitative Study. (15th July 2016) - Higgins, N.M.; Cochrane, A.; FitzGerald, O.; Gallagher, P.; Ashton, J.; Breen, R.; Brennan, A.; Corcoran, O.; Desmond, D.
Abstract : Background: Musculoskeletal disorders are amongst the leading causes of disability in the working age population. Growing evidence suggests early screening and targeted interventions during the acute phase can promote work retention and prevent disability. Objectives: This study aims to develop and feasibility test an early, case manager-led intervention focusing on work as a clinical outcome. Here we report qualitative findings from focus groups and interviews conducted to consider issues of content, delivery and optimal timing, and to explore key priorities and potential challenges in service delivery. Methods: Two focus groups and three individual interviews were conducted, involving 17 experts representing the multidisciplinary team. Thematic analysis was used to summarise the views and ideas expressed. Results: Participants highlighted the importance of early access to diagnosis, relevant investigations and referral to specialists as necessary in reducing the risk of long term disability; noting the critical importance of GPs in facilitating early access. The need to provide reassurance and education about the patient's condition was highlighted, as was the importance of screening for psychosocial risk factors. Patients most likely to benefit from the intervention were identified as those highly motivated to maintain their current work roles. Ready access to the MDT and the skill set of the case manager were noted as critical concerns, resource constraints pose considerable challenges. Conclusions: Introduction of an early integrated care intervention that targets risk of work disability is warranted. Considerable "buy-in" is required from all stakeholders involved. The data will help to inform the planned feasibility study. Acknowledgement: We would like to thank all of the individuals who participated in the interviews and focus groups. Disclosure of Interest: None declared